Proses Optimasi Masalah Penugasan One-Objective dan Two-Objective Menggunakan Metode Hungarian - Diang Dewi Tamimi; Ika Purnamasari; Wasono Wasono (Program Studi Statistika FMIPA Universitas Mulawarman, 2017)
Assignment problem is a situation where m workers are assigned to complete n tasks/jobs to minimize costs and time or maximize profits and quality by setting the proper task to each worker. Many researches have been focused to solve assignment problem, but most of them only consider one-objective such as minimizing the cost of operation. Two-objectiveassignment problem is the assignment problem that has two objectives optimization of some of the resources owned by each worker to complete every task/job which are cost and time for this case. Case in this research use primary data drawn from the interviews of Rattan furniture craftman in Rotan Sejati store, Samarinda. This research will optimize the one-objective and two-objective assignment problem by using Hungarian Method. The analysis result revealed that the optimization proccess of one-objective assignment problem only considering operation cost is Rp. 2.950.000,- with total time is 63 days. The optimization proccess of one-objective assignment problem only considering operation time is Rp. 3.290.000,- with total time is 52 days. The optimization proccess of one-objective assignment problem only considering quality is Rp. 3.550.000,- with total time is 59 days. The optimization proccess of two-objective assignment problem only considering operation cost and operation time is Rp. 3.170.000,- with total time is 52 days. The optimization proccess of two-objective assignment problem only considering operation cost and quality is Rp. 3.380.000,- with total time is 61 days. The optimization proccess of two-objective assignment problem only considering operation time and quality is Rp. 3.350.000,- with total time is 59 days.